An Analysis of Sixth Semester Students’ Ability in Comprehending Figurative Language in Poetry in English - Riska Mulyani; Delvi Wahyuni (Journal of English Language Teaching, 2022)
This study aims to determine the ability of sixth semester students in analyzing figurative language in English poetry. The participants in this study were 30 sixth semester students of English Education Study Program, Faculty of Language and Arts, Padang State University who took microteaching as a compulsory subject. This research is a descriptive research with a quantitative approach. The instrumentation of this research is a test. The test results in this study indicate that the level of student mastery in analyzing figurative language in English poetry is low. Based on the data taken in the test, metaphor is the most difficult element and simile is the easiest element. And it can be concluded that the students' ability to analyze the elements of English poetry is low